2009
DOI: 10.1017/s1368980008004503
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relative intake of fatty acids according to the Northern Sweden FFQ with fatty acid levels in erythrocyte membranes as biomarkers

Abstract: Objective: To evaluate the validity of the Northern Sweden eighty-four-item FFQ to estimate intake of fatty acids relative to 24 h diet recalls (24-HDR) and fatty acids in erythrocyte membranes. Design: Participants, randomly recruited from the population-based Västerbotten Intervention Project, answered the eighty-four-item FFQ. During the following year each participant carried out ten 24-HDR. Intake of fatty acids measured by the FFQ was compared with intake by the 24-HDR and fatty acid levels in erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 28 publications
6
51
0
1
Order By: Relevance
“…Post hoc analyses support this explanation since consumption frequencies from the FFQ showed almost the same consumption of wholegrain bread and white bread, while data from the 24-HDR showed that wholegrain bread contributed only 25 % of the consumed bread. The correlation coefficients between FFQ1 and the 24-HDR for absolute intakes of the individual plant sterols and total plant sterols were between 0?50 and 0?58 for the men, and between 0?43 and 0?55 for the women, and thus are comparable to those for other nutrients studied within this cohort (4)(5)(6) . As seen for most other nutrients, the correlation coefficients declined when energy-adjusted plant sterol intake was studied instead.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Post hoc analyses support this explanation since consumption frequencies from the FFQ showed almost the same consumption of wholegrain bread and white bread, while data from the 24-HDR showed that wholegrain bread contributed only 25 % of the consumed bread. The correlation coefficients between FFQ1 and the 24-HDR for absolute intakes of the individual plant sterols and total plant sterols were between 0?50 and 0?58 for the men, and between 0?43 and 0?55 for the women, and thus are comparable to those for other nutrients studied within this cohort (4)(5)(6) . As seen for most other nutrients, the correlation coefficients declined when energy-adjusted plant sterol intake was studied instead.…”
Section: Discussionsupporting
confidence: 65%
“…Previous publications from this diet database have examined the agreement between these two methods, focusing on the intakes of foods, energy, macronutrients and a selection of micronutrients (4) , fatty acids (6) , folate and other B vitamins (5) . These previous studies have concluded that the validity of the Northern Sweden FFQ is similar to that of other FFQ used in large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between 14:0 and insulin sensitivity may imply a favourable role of dairy intake on glucose metabolism, as suggested in some observational studies [2]. However, if this were the case, one would expect a similar pattern for 15:0 and 17:0, also considered closely associated with dairy intake when measured in serum [29] or erythrocyte membranes [30]. For 15:0, this was not significant in our study, suggesting that other dietary sources of 14:0, or endogenous metabolism, may contribute to the association, as also recently suggested by Roberts et al [19].…”
Section: Discussionmentioning
confidence: 74%
“…Total estimated daily intake of energy and nutrients was calculated by weighting reported intake frequencies by the food composition that is provided by the National Food Agency (http://www.livsmedelsverket.se/en/foodand-content/naringsamnen/livsmedelsdatabasen/). Estimated intakes of energy, nutrients, vitamins, and minerals have been validated against repeated 24-h dietary records and biological markers (28)(29)(30)(31).…”
Section: Dietary Assessmentsmentioning
confidence: 99%